2016
DOI: 10.1074/jbc.m116.751925
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Effects of the Bacterial Chaperonin GroEL on Fibrillogenic Polypeptides through Modification of Domain Hinge Architecture

Abstract: Edited by Paul FraserThe isolated apical domain of the Escherichia coli GroEL subunit displays the ability to suppress the irreversible fibrillation of numerous amyloid-forming polypeptides. In previous experiments, we have shown that mutating Gly-192 (located at hinge II that connects the apical domain and the intermediate domain) to a tryptophan results in an inactive chaperonin whose apical domain is disoriented. In this study, we have utilized this disruptive effect of Gly-192 mutation to our advantage, by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…We conclude that both Hsp60 WT and GW are stable tetradecamers, supporting a previous report [35]. Taken together with the results of GroEL G192W [24,30], we concluded that Hsp60 G190W had the open-mimic conformation of AD, similar to GroEL G192W, with hydrophobic characteristics that probably enhanced the amyloid fibrillation suppression effect. Comparing the structural characteristics of wild type (WT) and G190W Hsp60.…”
Section: Hsp60 Gw Shows An Increased Degree Of Surface Hydrophobicitysupporting
confidence: 88%
See 2 more Smart Citations
“…We conclude that both Hsp60 WT and GW are stable tetradecamers, supporting a previous report [35]. Taken together with the results of GroEL G192W [24,30], we concluded that Hsp60 G190W had the open-mimic conformation of AD, similar to GroEL G192W, with hydrophobic characteristics that probably enhanced the amyloid fibrillation suppression effect. Comparing the structural characteristics of wild type (WT) and G190W Hsp60.…”
Section: Hsp60 Gw Shows An Increased Degree Of Surface Hydrophobicitysupporting
confidence: 88%
“…Our previous studies showed that the GroEL G192W mutant "locks" the GroEL oligomer in an open conformation through introduction of tryptophan at hinge II site pushes AD upward. This enhances the affinity of GroEL G192W toward fibrillogenic polypeptides [24,30]. We intended to apply this method to human Hsp60 (Figure 1a) in this study.…”
Section: Open-mimic Mutant Hsp60 G190w (Gw) Is a Potent Suppressor Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the abundance of chaperonin GroEL (spot 1058; p-value = 0.006), universal stress protein (spot 3811), and quinoprotein ethanol dehydrogenase (spot 1001; p-value = 0.010) increased significantly during the time-course of biopolymer synthesis. GroEL, as the chaperonin family of molecular chaperones, is involved in the proper folding of many proteins [29]. Therefore, its increased abundance during P. putida KT2440 growth was important for aggregated proteins to renature after exposure to unfavorable conditions.…”
Section: Stress Responsementioning
confidence: 99%
“…In an effort analogous to our previous studies to use bacterial chaperones for protein aggregation control (14,15), we set out to probe the possibilities of using HdeA and HdeB in the control of irreversible aggregation and fibrillation of proteins, specifically at low pH. We began our experiments using human ␣-Synuclein because previous studies by Uversky et al (16) demonstrated that this protein forms fibrils more readily at lower pH (pH Ͻ5) than at neutral pH ( Fig.…”
mentioning
confidence: 99%